Effects of Different Chemical Forms of Nitrogen on the Quick and Reversible Inhibition of Soybean Nodule Growth and Nitrogen Fixation Activity - Yamashita, Natsumi; Tanabata, Sayuri; Ohtake, Norikuni; Sueyoshi, Kuni; Sato, Takashi; Higuchi, Kyoko; Saito, Akihiro; Ohyama, Takuji (Frontiers in Plant Science, 2019)
It has been reported that supply of nitrate to culture solution rapidly and reversibly inhibits nodule growth and nitrogen fixation activity of soybean. In this study, the effects of ammonium, urea, or glutamine on nodule growth and nitrogen fixation activity are compared with that for nitrate. Soybean plants were cultivated with a nitrogen-free nutrient solution, then 1 mM-N of nitrate, ammonium, glutamine, or urea were supplied from 12 DAP until 17 DAP. Repression of nodule growth and nitrogen fixation activity at 17 DAP were observed by ammonium, urea, and glutamine like nitrate, although the inhibitory effects were milder than nitrate. The removal of nitrogen from the culture solutions after nitrogen treatments resulted in a recovery of the nodule growth. It was found that the glutamine treatment followed by N-free cultivation gave highest nitrogen fixation activity about two times of the control. Tracer experiments with 15N and 13C were performed to evaluate the translocation of N and C to the different tissues. Culture solutions containing a 15N-labeled nitrogen source were supplied from 21 DAP, and the whole shoots were exposed to 13CO2 for 60 min on 23 DAP, and plants were harvested on 24 DAP. The percentage distribution of 15N in nodules was highest for ammonium (1.4%) followed by glutamine (0.78%), urea (0.32%) and nitrate (0.25%). The percentage distribution of 13C in the nodules was highest for the control (11.5%) followed by urea (5.8%), glutamine (2.6%), ammonium (2.3%), and nitrate (2.3%). The inhibitory effects of nitrogen compounds appeared to be related to a decrease in photoassimilate partitioning in the nodules, rather than 15N transport into the nodules. The free amino acid concentrations after nitrogen treatments were increased in the nodules and leaves by nitrate, in the roots by ammonium, in the stems by urea, and the roots, stems and leaves by glutamine treatment. The concentrations of asparagine, aspartate, and glutamine were increased after nitrogen treatments. By the long-term supply of nitrogen for 2-weeks, nitrate significantly increased the lateral roots and leaf growth. The long-term supply of urea and glutamine also promoted the lateral roots and leaf growth, but ammonium suppressed them.